RESPONS MAHASISWA TERHADAP PERKULIAHAN PADA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS SURYAKANCANA TAHUN 2015/2016 - Siti Maryam (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2017)
This article describes the response of the students to lecture on Language and Literature Indonesian Departement FKIP Suryakancana University, covering eight aspects, namely the response of students to the quality of lecture material, mastery lecturers to lecture material it presents, the strategy of the course, the effectiveness of student groups, service faculty to students, use of time allocation, utilization of instructional media, and organizing classes. The research uses descriptive method by using a research technique Bull Eyes. The results showed that the response of students to the eighth aspects studied well the average category. Not up to the results of this study will be used to improve the quality of the lecture and improve the competence of lecturers and graduate Language and Literature Indonesian Departement FKIP Suryakancana University.